Prince Lichtenstein's Museum - Sandmann, François-Joseph, 1805-1852 (lithographer):::Creator::::::::::::; Alt, Rudolf von, 1812-1905 (artist):::Contributor:::::::::::: (Austria; H.F. Miller; Vienna)
Color lithograph of the Liechtenstein Museum in Vienna